Parytety i kwoty wyborcze a Konstytucja RP - Urbaniak, Krzysztof (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The issue of intensifying female participation in public life, and particularly in political life, has recently been the subject of lively discussions, in particular in the social sciences. The number of female candidates on the election ballots for representative organs is clearly insuf- ficient in comparison to the size of the female electorate, as well as the abilities, skills and in- tellectual potential women occupy. This problem has also been widely discussed in Poland. As a result of these quite heated disputes and discussions, accompanied by an interesting ex- change of views on the doctrine of electoral law, an instrument to increase female representa- tion on election ballots (a quota system) was introduced into the Polish electoral system. The subject of this paper, however, is not the issue of the grounds or justification for the legal in- struments applied, or an assessment of the activities of the state authorities or the institutions of public life in this respect. Rather, the paper analyzes the legal solutions introduced in Po- land in order to increase the political participation of women from the point of view of their conformity with the regulations of the Constitution of the Polish Republic. For this purpose, the author refers both to the doctrine of constitutional law and the adjudications of the Consti- tutional Tribunal. This analysis leads to the conclusion that the ‘compensatory privilege’, in- troduced in law, is highly questionable in terms of its conformity with the Polish Constitution. In this light an amendment to the Constitution would be recommended, providing a constitu- tional status to the provisions on equality.
Parity and Electoral Quotas versus the Constitution of the Polish Republic
Keywords: parytet; kwoty wyborcze